2021
DOI: 10.1186/s12916-021-02153-8
|View full text |Cite
|
Sign up to set email alerts
|

Predicted norovirus resurgence in 2021–2022 due to the relaxation of nonpharmaceutical interventions associated with COVID-19 restrictions in England: a mathematical modeling study

Abstract: Background To reduce the coronavirus disease burden in England, along with many other countries, the government implemented a package of non-pharmaceutical interventions (NPIs) that have also impacted other transmissible infectious diseases such as norovirus. It is unclear what future norovirus disease incidence is likely to look like upon lifting these restrictions. Methods Here we use a mathematical model of norovirus fitted to community incidenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 52 publications
2
19
0
2
Order By: Relevance
“…Our results show that the social restrictions reduced the visits due to gastroenteritis and both norovirus and rotavirus detections in Finnish children. Our results are in line with the previous reports from Germany, England and China, 1–4 which showed that the norovirus and rotavirus detections decreased rapidly after the restrictions were implemented. Interestingly, we report a much later increase in the incidence of norovirus than the previous report from Hong Kong, 5 although Finland relaxed the restrictions much earlier.…”
Section: Figuresupporting
confidence: 93%
See 2 more Smart Citations
“…Our results show that the social restrictions reduced the visits due to gastroenteritis and both norovirus and rotavirus detections in Finnish children. Our results are in line with the previous reports from Germany, England and China, 1–4 which showed that the norovirus and rotavirus detections decreased rapidly after the restrictions were implemented. Interestingly, we report a much later increase in the incidence of norovirus than the previous report from Hong Kong, 5 although Finland relaxed the restrictions much earlier.…”
Section: Figuresupporting
confidence: 93%
“…As the restrictions have been relaxed, there has been concern that the norovirus and rotavirus cases would start to increase rapidly. The year 2021 was also predicted to have a high incidence of cases of norovirus and rotavirus as modelling studies suggested a possible two‐fold increase in the detections compared with the pre‐pandemic era 3,4 . Interestingly, a study from Hong Kong reported that despite continuous restrictions, the norovirus and rotavirus cases returned near to pre‐pandemic levels 5 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Resurgence of norovirus incidence after relaxation of non-pharmaceutical interventions related to SARS-CoV2 pandemic has been predicted [161]. Continued surveillance should be encouraged to allow adequate preparation for a potential increase in healthcare pressures beyond previous levels.…”
Section: Lessons From the "Coronavirus Pandemic"mentioning
confidence: 99%
“…Throughout the COVID-19 pandemic, machine learning and artificial intelligence (AI) methods have been used to understand and predict virus spread, the potential impact of vaccines, morbidity, mortality, and resource allocation [ 1 ]. Modeling of COVID-19 morbidity and mortality has yielded insights into disease progression [ 2 , 3 ], which have been informative for health systems to anticipate resource needs and effective interventions [ 4 ]. However, with the emergence of COVID-19 variants and rapid advances in COVID-19 treatment, prevention, and vaccination, 1-time modeling is likely ineffective for understanding how to provide optimal care from the patient, health system, and public health perspectives [ 4 ].…”
Section: Introductionmentioning
confidence: 99%